Proposed change in status of the Nearctic genus Charadrodromia Melander (Diptera: Hybotidae, Tachydromiinae), with description of four new species - Shamshev, Igor; Grootaert, Patrick (Zootaxa, 2012)
The genus Charadrodromia Melander is reviewed and considered here as a junior synonym of Platypalpus Macquart. All three species originally included in the former group are re-described (P. arnaudi (Melander, 1960) comb. nov., P. microphona (Melander, 1928) comb. nov., P. syletor (Melander, 1928) comb. nov.); the photos of the habitus for each species based on the type specimens are provided; the male of P. syletor is described for the first time; and the lectotype of P. microphona is designated. Also, among unidentified materials assigned to the former Charadrodromia four new species are revealed: P. cummingi Shamshev & Grootaert sp. nov. (USA, California), P. layiaphilus Shamshev & Grootaert sp. nov. (USA, California), P. submicrophona Shamshev & Grootaert sp. nov. (USA, California), P. tanbarkiensis Shamshev & Grootaert sp. nov. (USA, California). The lectotype of the related P. canus Melander, 1902 is designated, the species is re-described, and figures of male terminalia are provided for the first time. The systematic position of species assigned to the former Charadrodromia is discussed and they are provisionally assigned to the P. hackmani group previously known from the Palaearctic. A key to the eight included species is provided.